A subordinação na relação individual de emprego contemporânea - Macagnan, Fabio Rogério Del Arco (2020)
This study seeks to understand the new face of subordination in the individual relationship of contemporary employment, as well as to verify if there is a violation of human and fundamental rights, especially of workers of the contemporary era. From this, it is proposed to describe the state of affairs of subordination and to debate its effectiveness and effectiveness of these rights between employee and employer, who, as private individuals, are subject to fundamental rights and guarantees. The technical procedures for this investigation were blibliographical, documentary and theoretical-normative research.